Hukum Puasa Untuk Kelulusan Anak - Nur Cholishotul Islamiyah; Bakhruddin Fannani (Riviera Publishing, 2025)
The phenomenon of fasting for a child’s graduation has become a socio-religious practice found in various regions of Indonesia. This tradition is performed by parents or guardians as a spiritual effort for their children’s success in school examinations or admission to higher education. This study aims to analyze the legal ruling (hukm) of fasting for a child’s graduation from the perspective of Islamic law, focusing on the aspects of intention, purpose, and practice. The research employs a library study with a normative-theological approach based on the Qur’an, Hadith, and classical jurists’ opinions. The findings indicate that fasting for a child’s graduation is permissible as long as it is not associated with mystical beliefs and is intended as an act of worship to draw closer to Allah SWT. This practice can be categorized as tathawwu’ fasting (voluntary fasting), which carries spiritual merit when combined with lawful effort and supplication. However, if it is believed to be the absolute cause of success without rational effort, the practice may fall into superstition or innovation (bid’ah) that requires correction.